KONSEP NULITAS DALAM KONTRAK PENGADAAN BARANG ATAU JASA YANG DIKERJAKAN OLEH PIHAK PEMINJAM NAMA PERUSAHAAN - Bintang Puwan Permata (The Juris, 2023)
The Commitment Officer as the services user is the aggrieved party in a procurement contract for goods/services signed and/or executed by the party borrowing the company’s identity. This is because the work is carried out by a party who, legally, lacks the authority and legitimate position and cannot be directly held accountable for the executed work. Consequently, delays and a decrease in quality may occur in line with the specified technical specifications. This article aims to provide an overview for parties involved in government procurement contracts regarding the consequences and legal actions that can be taken in the event of a dispute over a government procurement contract signed and/or executed by a party borrowing the company’s identity. This way, it can anticipate potential adverse situations. This article is a normative legal writing using legislative and conceptual approaches. The data used include primary legal materials and secondary legal materials analyzed through deductive reasoning. The concept of null and void applies to agreements involving borrowing a company’s name with the intention of directing the tender to be won by a participant under its control. On the other hand, for agreements involving borrowing a company’s name made on the grounds of not having a company or business entity that meets tender requirements, the concept of cancellability applies.